2008
DOI: 10.1159/000187686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basic Fibroblast Growth Factor in Transgenic Mice: Corneal Epithelial Healing Process after Excimer Laser Photoablation

Abstract: Purpose: To evaluate the role of preparedbasic fibroblast growth factor (bFGF) eyedrops in corneal epithelial healing of transgenic mice after excimer laser photoablation. Materials and Methods: In our prospective case series, 60 eyes of 30 mice had uneventful bilateral excimer laser photoablation. In each mouse, 1 eye received the standard topical postoperative therapy with tobramicin, diclofenac and dexamethasone eyedrops, plusbFGF eyedrops 5 μg/10 μl PBS 3 times a day for 1 week, or until corneal reepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…The degree and extent of keratocyte apoptosis also varies with the type of overlying epithelial injury, and can be influenced by the surgical technique and drugs. [121314151617181920212223242526272829303132333435363738394041424344454647] Therefore, rapid re-epithelialization of the cornea would likely promote wound healing of the underlying stroma with minimal cell apoptosis. [38] Furthermore, the identification of factors that aid re-epithelialization after corneal epithelial injury and prevent complications related to delayed cicatrization, such as scar or haze formation, would optimize surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree and extent of keratocyte apoptosis also varies with the type of overlying epithelial injury, and can be influenced by the surgical technique and drugs. [121314151617181920212223242526272829303132333435363738394041424344454647] Therefore, rapid re-epithelialization of the cornea would likely promote wound healing of the underlying stroma with minimal cell apoptosis. [38] Furthermore, the identification of factors that aid re-epithelialization after corneal epithelial injury and prevent complications related to delayed cicatrization, such as scar or haze formation, would optimize surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the efficacy of recombinant human b-FGF on epithelial healing has been demonstrated in rabbits after mechanical anterior keratectomy. [31323334354445]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some groups have reported that topical EGF application increased the wound-healing rate in vivo, but others reported no benefit. Moreover, a recent study showed that eye drops containing bFGF significantly accelerated epithelial healing after LASEK by increasing corneal reepithelialization in transgenic mice (28).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the epithelial damage and of the loss of the intact basement membrane function, also stromal cells and keratocytes secrete cytokines in order to modulate the proliferation, migration and differentiation of epithelial and stromal cells into fibroblasts and myofibroblasts [3,9] and to repair the stroma [6].In rabbit models, the topical application of a variety of molecules is able to promote the corneal repair process leading to a better wound healing; among the tested factors, can be mentioned the plasma rich in growth factors (PRGF-Endoret) [10], the ascorbic acid [11], the nerve growth factor (NGF) in combination with docosahexaenoic acid (DHA) [12], the vitamin E and hydrocortisone acetate [13], and finally the basic fibroblast growth factor (bFGF) [14,15] can be mentioned. Moreover we previously showed that, in transgenic mice, topical cytochrome c peroxidase [16], bFGF alone [17], or in combination with cytochrome c [18] and oral administration of l-cysteine [19] significantly accelerates epithelial healing after excimer photoablation. Despite the limits of the animal models, which are the different physiology and the short term evaluation, we found that these observations were a useful starting point to test the efficacy of supplementation strategies in humans.…”
mentioning
confidence: 99%